下顎歯肉癌を生じたCowden症候群の1例 - 平岡, 佑二郎; 重岡, 学; 南川, 勉; 榎本, 由依; 古森, 孝英; 明石, 昌也 (日本口腔外科学会雑誌, 2018)
Cowden's syndrome is a rare genodermatosis of autosomal dominant inheritance and variable phenotype, principally characterized clinically by multiple hamartomas in various organs, including the skin, thyroid, and gastrointestinal tract and by an increased risk for the development of malignancy. We report a case of Cowden's syndrome associated with oral squamous cell carcinoma of the lower gingiva. A 65-year-old man was referred to our hospital because of swelling of the right lower gingiva, and a biopsy of the right lower gingiva revealed squamous cell carcinoma. Preoperative upper gastrointestinal endoscopy showed multiple polypoid lesions in both the esophagus and the stomach. In addition, there were papillomatous lesions in the oral mucosa. On the basis of these clinical findings, Cowden's syndrome was suspected. Whole body positronemission tomography and computed tomography showed mass shadows in the right mandible and the right submandibular lymph nodes. Surgery was performed, and the final histopathological diagnosis was squamous cell carcinoma. Taken together, we diagnosed Cowden's syndrome accompanied by oral cancer. The patient is currently under follow-up observation in our department.